(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
In this article, the question of the application of the technology of didactic unit approximation of future mathematics shooters in the conditions of innovative education today is justified, or rather, the fact that it can be used in the training of basic concepts of umatematic analysis on the basis of contextual education, on the example of the first excellent limit.